Prevalence of microorganism in cell phone and the behavioral pattern associated with the demographic of Dhaka City (North) - Saif, Nasif Bin (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.